'I'm me, and I'm Chinese and also transgender': coming out complexities of Asian-Canadian transgender youth. Issue 2 (3rd April 2023) - Tan, Sulin; Weisbart, Cindy
Abstract: The complexities of developing and disclosing multiple, marginalized, minority identities is theoretically recognized by Minority Stress Theory and the concept of intersectionality; however, the experiences of people living at these intersections, such as Asian transgender youth, are under-examined. Consequently, they remain a largely erased community, often excluded from the research and services that are assumed to include them. The present study attempted to ameliorate this erasure by examining the coming out experiences of eight Asian-Canadian transgender youth. Interpretative phenomenological analysis (IPA) was utilized from Minority Stress Theory and intersectional perspectives to advance understanding of their coming out experiences and the contexts that maintain their marginalization. Semi-structured individual interviews elicited three themes: (a) Maintaining Family Cohesion; (b) Experiencing Adultism; and (c) Creating Community. Implications for service provision and future research are discussed with emphasis on attending to their whole personhood, which necessarily includes the individual, their community, and the systemic structures that perpetuate oppression.